2012
DOI: 10.1016/j.jns.2011.09.013
|View full text |Cite
|
Sign up to set email alerts
|

A novel nonsense mutation in the TITF-1 gene in a Japanese family with benign hereditary chorea

Abstract: A Japanese family with a novel nonsense mutation in the TITF-1 gene (p.Y98X) is described.The proband showed severe generalized chorea, delayed motor development, subnormal intelligence, congenital hypothyroidism, bronchial asthma, and a history of pulmonary infection, all of which are characteristic features of Brain-Thyroid-Lung syndrome. On the other hand, her brother and mother showed a mild benign hereditary chorea (BHC) phenotype with congenital hypothyroidism.Intrafamilial phenotypic variation is common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 35 publications
1
21
2
Order By: Relevance
“…Thyroid transcription factor 1 protein also plays an important role in thyroid and lung organogenesis . Previous reviews have suggested that approximately half of all individuals with NKX2.1 mutations have the full triad of brain, lung, and thyroid involvement . However, in our series only three out of 10 individuals had involvement of all three organs, despite comprehensive investigation.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Thyroid transcription factor 1 protein also plays an important role in thyroid and lung organogenesis . Previous reviews have suggested that approximately half of all individuals with NKX2.1 mutations have the full triad of brain, lung, and thyroid involvement . However, in our series only three out of 10 individuals had involvement of all three organs, despite comprehensive investigation.…”
Section: Discussioncontrasting
confidence: 72%
“…Linkage analysis and positional cloning have identified NKX2.1 as the causative gene, located on chromosome 14q13 (also known as TITF1 , TTF‐1 , TEBP , and NKX2A) . More than 30 different mutations of this gene have been identified to date including whole‐gene deletions as well as splice‐site, frameshift, nonsense, and missense mutations …”
mentioning
confidence: 99%
“…Despite the severe impact on the TITF1 protein, which is usually caused by loss of function mutations, the observed clinical manifestations are variable. Other reported patients with loss of function mutations exhibited a phenotype ranging from BHC to the more severe brain‐thyroid‐lung syndrome, with variable severity even in the same family . More than 90 TITF1 mutations have been reported to date, but attempts to make genotype‐phenotype correlations have remained unsuccessful.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital hypothyroidism can be divided into two major types according to its pathogenesis. 80%-85% of CH is caused by defective thyroid glands, such as athyreosis, hypoplastic or ectopic gland [4] ,which is closely related to the gene encoding thyroid transcription factor, such as TSHR [5] , TTF1 [6] ,PAX8 [7] ,NKX2.1 [8] and FOXE1 [9] and so on. 15%-20% of CH patients with thyroid dyshormonogenesis combined with thyroid goiter [1] is inherited as an autosomal recessive trait [10] .…”
Section: Introductionmentioning
confidence: 99%